Wiedza i zmysły w pracy tłumacza - Muszyńska‑Vizintin, Anna (Przekłady Literatur Słowiańskich, 2015)
The role of translator’s erudition and sensory cognizance in the process of translation This paper deals with the problem of literary texts (such as. Historical novels, diaries, travelogues, biographies, literary essays, etc.) which are characterized by a high degree of reality (category mimesis) and by realistic descriptions of the available spaces, buildings, art, etc. This type of literature requires a certain knowledge and erudition from the translator, and it is often based on real experiences which are connected to the senses (sound, sight, touch, smell, taste), but in particular with sight (figure hipotiposis). An interesting example, that somehow brings together the problems of knowledge and sensory perception in the process of translation, are the travelogue essays on art, characterized by the rhetorical figure known as ekphrasis — a “verbal (linguistic) description of an existent art object”. From the perspective of the theory of translation, travelogue essays concerning art (eg. Zbigniew Herbert‑collection “Barbarian in the garden”) imply the existence of two types of translation, which are: 1) intersemiotic translation (transmutation) and; 2) interlingual translation (from one language to another). During the process of interlingual translation it would be recommendable for the translator to also include the dynamics of transmutation, that is to verify the correctness of the translation in comparison to the original text as well as to the art object, described in the original text. Key words: mimetic literature (mimesis), translator’s erudition, sensory cognizance, ekphrasis, essay about visual arts